Small-amplitude oscillations of magnetization accompanying long-lived spin-precession in ³He-B - Kharadze, G. A.; Suramlishvili, N.G.; Vachnadze, G.E. (Физика низких температур, 1997)
Frequency spectrum of small-amplitude oscillations of magnetization against the background of coherently precessing (phase-correlated) spin modes in superfluid ³He placed in a strong magnetic field depends on the magnitude of spin polarization S and spin-orbit structure of dynamical ordered states. Spectrum of these oscillations is calculated for unconventional precessing modes in ³He-B characterized by S=S₀/2, where S₀ is the value of S at equilibrium.